Cluster Preface: Synthesis of Energetic Molecules - Huang, Haifeng; Yang, Jun (Synlett, 2024)
is a professor at Shanghai Institute of Organic Chemistry, Chinese Academy of Sciences, Shanghai, P.R. China. He received his Ph.D. in 2012 from Beijing Institute of Technology (BIT) under the guidance of Prof. Zhiming Zhou. Then, he joined Shanghai Institute of Organic Chemistry to start his academic career. His research interests mainly focus on the design and synthesis of new energetic materials.Jun Yang received his Ph.D. at Shanghai Institute of Organic Chemistry, Chinese Academy of Sciences in 2005 under the supervision of Prof. Minzhi Deng. He is now a professor of the Shanghai Institute of Organic Chemistry, CAS. His research interests primarily include the synthesis of energetic materials and energy regulation materials for solid and liquid propellants.